2006
DOI: 10.1002/mus.20580
|View full text |Cite
|
Sign up to set email alerts
|

Sural neuropathy: Etiologies and predisposing factors

Abstract: Isolated sural neuropathy is an uncommon diagnosis. We identified 36 patients with isolated sural neuropathy. Sixteen had various forms of ankle trauma, in three of whom the associated sural neuropathies developed following medical intervention. Three patients developed sural neuropathy associated with vasculitis, and there were single patients with schwannoma and ganglionic cyst. In patients without a history of trauma, structural causes, such as schwannoma or ganglionic cysts and vasculitis, should be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…We read with interest the article by Stickler et al 5 about etiologies and predisposing factors of sural nerve lesions. In their short anatomical review, the authors assume that the sural nerve is a purely sensory nerve.…”
mentioning
confidence: 95%
“…We read with interest the article by Stickler et al 5 about etiologies and predisposing factors of sural nerve lesions. In their short anatomical review, the authors assume that the sural nerve is a purely sensory nerve.…”
mentioning
confidence: 95%
“…In a series of 36 cases with isolated sural neuropathy, Stickler and colleagues reported 16 patients with ankle trauma, three with vasculitis, and one patient each with schwannoma and ganglionic cyst [8]. Ganglionic cysts of the sural nerve have also been described by other authors [10][11][12].…”
Section: Non-neoplastic Focal Lesionsmentioning
confidence: 89%
“…Schwannomas and other nerve sheath tumors rarely affect nerves used for diagnostic biopsy in an isolated manner [8]. In contrast, involvement of such nerves by socalled schwannoid tumorlets is common in neuropathies in the context of neurofibromatosis-2 (see Chapter 23).…”
Section: Non-malignant Neoplastic Lesionsmentioning
confidence: 99%
“…Sural nerve pathology is an uncommon diagnosis (Stickler et al, 2006), but is a condition that may be overlooked as differential diagnosis. For example, a retrospective analysis of 18 elite athletes with suspected chronic Achilles tendinopathy who failed conservative tendon management revealed that sural nerve entrapment was the cause of the symptoms (Fabre et al, 2000).…”
Section: Introductionmentioning
confidence: 99%